Inheritance Practices and Widow's Economic Vulnerability: A Case Study of Rural Communities in Yakurr Local Government Area - Inyang Etim Bassey (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
This study examines the relationship between customary inheritance practices and the economic vulnerability of widows in rural communities of Yakurr Local Government Area, Cross River State, Nigeria. Despite constitutional guarantees and international human rights commitments affirming women's equal rights to inherit property, widows in these communities experience systematic dispossession following their husbands' deaths. Employing a qualitative case study design, the research draws on in-depth interviews with thirty widows, focus group discussions with community members, and key informant interviews with traditional rulers, women leaders, and paralegal workers. The study is theoretically grounded in feminist legal theory, the capability approach, and legal pluralism. Findings reveal that inheritance practices in Yakurr operate through patrilineal principles that classify widows as outsiders to their husbands' lineages, rendering them ineligible to inherit land, homes, or productive assets. These practices create severe economic vulnerability manifested in loss of housing, exclusion from agricultural land, depletion of household assets, and increased dependence on extended family networks. The study identifies variations in widows' experiences based on factors including presence of adult sons, duration of marriage, personal agency, and access to external support. Widows navigate these constraints through strategies including appeals to traditional authorities, reliance on children, engagement in precarious livelihoods, and in rare cases, pursuit of statutory legal remedies. The study concludes that addressing widows' economic vulnerability requires interventions that engage with customary institutions while promoting incremental reform, strengthening paralegal support, and building community awareness of women's rights.